2009
DOI: 10.1016/j.ijrobp.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Preradiotherapy Chemotherapy Followed by Hyperfractionated Radiotherapy for Newly Diagnosed High-Risk Medulloblastoma/Primitive Neuroectodermal Tumor: A Report From the Children's Oncology Group (CCG 9931)

Abstract: Corresponding author: Jeffrey Allen, NYU Medical Center, 160 E. 32 nd St, Hassenfeld Clinic, New York, NY 10016 Tel: (212) Fax (212) Conflicts of Interest Notification: nonePublisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final citable form. Ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 26 publications
2
28
1
1
Order By: Relevance
“…Although several epidemiologic studies have included medulloblastomas and PNETs together as a single entity, [22][23][24][25][26] a landmark study has identified genetic differences that point to a difference in cell origin between these 2 tumor types. 27 The inclusion of both histologic subtypes into the regression model was because PNETs were distributed similarly across age groups (see Table 1); therefore, any survival differences between tumor types would result in differences that were consistent across age categories and would not alter the overall differences between age groups, which was the key issue addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although several epidemiologic studies have included medulloblastomas and PNETs together as a single entity, [22][23][24][25][26] a landmark study has identified genetic differences that point to a difference in cell origin between these 2 tumor types. 27 The inclusion of both histologic subtypes into the regression model was because PNETs were distributed similarly across age groups (see Table 1); therefore, any survival differences between tumor types would result in differences that were consistent across age categories and would not alter the overall differences between age groups, which was the key issue addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Whereas 80% of children with localized MB will be cured following treatment with reduced dose craniospinal radiation therapy (CSRT) and chemotherapy, 3 the success rate for patients with disseminated disease, as well as for those with supratentorial primitive neuroectodermal tumors (PNETs), has historically been poor despite full-dose CSRT and chemotherapy. 1,[4][5][6] The Goldie-Coldman model of therapeutic resistance states that the prompt elimination of tumor through the use of multiple drugs given concurrently reduces the likelihood of the emergence of resistant clones. 7 CSRT is the most effective treatment modality against MB and can be modeled as a non-cross-resistant chemotherapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…The German HIT'91 trial showed superior results with post operative RT followed by CCNU, vincristine and cisplatin compared to postoperative ifosfamide, etoposide, highdose methotrexate, cisplatin and cytosine arabinoside followed by irradiation: 83% 5-year EFS compared to 53%, respectively for M0 patients; no difference was noted in the M2-3 cohort, both at 40% EFS (127). CCG 9931 documented a 17% PD rate during a prolonged, 5 month preirradiation regimen, again showing only 43% EFS in high-risk disease (121). Similar trials have noted that outcome in average-risk patients receiving preirradiation CT correlates with response to CT; in the Milan trial, those with CR-PR to preirradiation CT enjoyed 94% PFS compared to 61% if only SD or PD attended CT (128).…”
Section: Chemotherapymentioning
confidence: 92%
“…The result is systematic reduction in CSI dosage to 23.4 Gy; with well documented efficacy now in average-risk disease when combined with contemporary cisplatin based CT (116,117). Agreement on combined chemo radiation is based on disease control rates that appear to be superior to those achieved with irradiation alone for both average-risk and high-risk presentations, a randomized European trial demonstrating improved outcome with chemo radiation compared to contemporary RT alone and several studies suggesting improvement in the risk: benefit ratio based on dose-volume modeling and evolving clinical data (118,119,120,121).…”
Section: Radiation Therapymentioning
confidence: 99%